EFFORTS TO IMPROVE ENTREPRENEURSHIP BASED ON CREATIVE ECONOMY IN DETERMINING THE SELLING PRICE OF ENVIRONMENTALLY FRIENDLY SOAP - Riaty Handayani; Sely Megawati Wahyudi (Jurnal Industri Kreatif dan Kewirausahaan, 2025)
Community empowerment, particularly for women's groups (PKK), is a crucial strategy for improving economic and social well-being, and environmental preservation. One effective way is through the development of entrepreneurship based on environmentally friendly products, such as dishwashing soap made from natural ingredients that are safe for the body and the environment. The production of environmentally friendly dishwashing soap can be a solution to public health and environmental degradation. However, several challenges faced by PKK women and MSMEs in North Meruya Village include a lack of knowledge about environmentally friendly materials, leading them to use hazardous chemicals in dishwashing soap production; limited knowledge about the health benefits of eco-friendly soap and its impact on the ecosystem; and difficulty calculating competitive product prices due to a lack of understanding of detailed production cost calculations.The discussion and question-and-answer sessions are an important part of community service activities because they provide a space for participants to clarify any unclear material, share experiences or challenges during practice, and delve deeper into business opportunities and the sustainability of the activities. The result of this training is that the PKK mothers have additional knowledge in implementing environmentally friendly soap making practices and calculating production costs which can ultimately determine the selling price of the product, thereby increasing entrepreneurship.